The Effect of Electrical Stimulation–Induced Pain on Time Perception and Relationships to Pain-Related Emotional and Cognitive Factors: A Temporal Bisection Task and Questionnaire–Based Study - Weng, Chun-Chun; Wang, Ning; Zhang, Yu-Han; Wang, Jin-Yan; Luo, Fei (Frontiers in Psychology, 2022)
Pain has not only sensory, but also emotional and cognitive, components. Some studies have explored the effect of pain on time perception, but the results remain controversial. Whether individual pain-related emotional and cognitive factors play roles in this process should also be explored. In this study, we investigated the effect of electrical stimulation–induced pain on interval timing using a temporal bisection task. During each task session, subjects received one of five types of stimulation randomly: no stimulus and 100 and 300 ms of non-painful and painful stimulation. Pain-related emotional and cognitive factors were measured using a series of questionnaires. The proportion of “long” judgments of a 1200-ms visual stimulus duration was significantly smaller with 300 ms painful stimulation than with no stimulus (P < 0.0001) and 100 ms (P < 0.0001) and 300 ms (P = 0.021) non-painful stimulation. The point of subjective equality (PSE) did not differ among sessions, but the average Weber fraction (WF) was higher for painful sessions than for no-stimulus session (P = 0.022). The pain fear score correlated positively with the PSE under 100 ms non-painful (P = 0.031) and painful (P = 0.002) and 300 ms painful (P = 0.006) stimulation. Pain catastrophizing and pain anxiety scores correlated significantly with the WF under no stimulus (P = 0.005) and 100 ms non-painful stimulation (P = 0.027), respectively. These results suggest that electrical stimulation–induced pain affects temporal sensitivity, and that pain-related emotional and cognitive factors are associated with the processing of time perception.